2016
DOI: 10.1093/jac/dkv456
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy with minocycline or trimethoprim/sulfamethoxazole for treatment ofStenotrophomonas maltophiliainfections

Abstract: Treatment failure did not differ between patients receiving trimethoprim/sulfamethoxazole or minocycline monotherapy for treatment of S. maltophilia infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 19 publications
3
56
1
Order By: Relevance
“…18 Researchers evaluated minocycline monotherapy versus trimethoprim-sulfamethoxazole monotherapy for the treatment of S. maltophilia infections. 19 Patients with at least one positive culture for S. maltophilia were identified by retrospective chart review from January 2006 to December 2012 at University Hospital in San Antonio, Texas. The primary objective was to compare rates of treatment failure between the two groups, which was defined as isolation of S. maltophilia on follow-up culture from the same site within 30 days, in-hospital death within 30 days of the original positive culture, or receipt of an alternative or additional antibiotic with in vitro activity for S. maltophilia.…”
Section: Clinical Treatment Datamentioning
confidence: 99%
See 2 more Smart Citations
“…18 Researchers evaluated minocycline monotherapy versus trimethoprim-sulfamethoxazole monotherapy for the treatment of S. maltophilia infections. 19 Patients with at least one positive culture for S. maltophilia were identified by retrospective chart review from January 2006 to December 2012 at University Hospital in San Antonio, Texas. The primary objective was to compare rates of treatment failure between the two groups, which was defined as isolation of S. maltophilia on follow-up culture from the same site within 30 days, in-hospital death within 30 days of the original positive culture, or receipt of an alternative or additional antibiotic with in vitro activity for S. maltophilia.…”
Section: Clinical Treatment Datamentioning
confidence: 99%
“…Treatment failure at 30 days did not differ significantly between the two groups (minocycline 30% versus trimethoprim-sulfamethoxazole 41%; p=0.67). 19 Tigecycline is another potential alternative. A group conducted a retrospective cohort study between 2008 and 2010 at a tertiary care hospital in Turkey in order to compare the efficacy of tigecycline to trimethoprim-sulfamethoxazole for nosocomial S. maltophilia infections.…”
Section: Clinical Treatment Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, resistance to levofloxacin appears to be increasing, particularly in the setting of fluoroquinolone prophylaxis, which limits its use as empirical therapy [93,94]. Other potential treatment options include tigecycline and minocycline [85,95]. …”
Section: Stenotrophomonas Maltophiliamentioning
confidence: 99%
“…However, TMP-SMX-resistant strains have been increasingly reported [16] , [17] and the TMP-SMX intolerance or allergic reactions are not uncommon. Hand et al reported that treatment failure did not differ between TMP-SMX and MINO monotherapies for S. maltophilia infections [18] . Accordingly, we selected intravenous MINO and oral LVFX antibiotic therapy with drainage of the abscess and successfully treated this patient.…”
Section: Discussionmentioning
confidence: 99%